The struggling state : nationalism, mass militarization, and the education of Eritrea - Riggan, Jennifer (2016)
The struggling state explores Eritreans’ disillusion with a government that permanently conscripts the vast majority of its citizens into the military, and examines teachers’ paradoxical roles as educators who are trying to create a bright and peaceful future for the nation while situated to shuttle their students into the military.